Peristaltic transport of a particulate suspension in the small intestine - Sinnott, Matthew D.; Cleary, Paul W.; Harrison, Simon M. (Applied Mathematical Modelling, 2017)
•A digestive transport model with multiphase content and compliant walls is proposed.•Vortical flow drives radial transport, nutrient absorption, and mixing of content.•Non-uniform solids distribution along the gut lead to changes in content rheology.•Presence of solids in digesta reduces intestinal mass flow rate.•Tethering of gut wall stops development of transverse instability for fluid content. Food transport through different sections of the gastrointestinal tract for the purposes of digestion and waste removal is an essential physiological function for life. Mechanical and chemical breakdown of food takes place throughout the gastrointestinal tract. Periodic muscular contraction and relaxation of the intestinal walls agitate, mix and propel the multiphase digesta along the intestines. Experimental measurement of flow inside the intestines is difficult therefore understanding of food transport through the majority of the gut is limited. Computational models for predicting the transient behaviour of intestinal content subject to peristaltic activity offer the possibility for assessing the digestive performance of different foods. We present a numerical model for peristalsis in the duodenum using a suspension of rigid particulates in a viscous Newtonian fluid to represent simple digesta. This consists of a thin viscoelastic membrane representing the gut wall coupled to the particle-based methods Smoothed Particle Hydrodynamics (SPH) and Discrete Element Method (DEM) which are used to predict the motion of liquid and solids content respectively. Peristaltic waves travel along the gut wall resulting in active muscular contractions and relaxations of the gut. The bulk motion of the content shows both phases move together due to the laminar nature of the flow with only very short-term inter-phase differences found in the relaxation region and in the wake of the contraction. Propulsive events were found to cause significant non-homogeneity of the solids distribution along the length of the duodenum. The inclusion of solids mildly modifies the overall propulsive flow behaviour and the retrograde jet in the wake of the contraction. In the absence of solids and connective tissue constraints, a transverse wobbling instability in the fluid filled viscoelastic tube is observed.